Treatment of Onychomycosis: An Update - Shirwaikar, A. A. (Medknow Publications, 2008)
Fungal infections of skin are one of the most common infections in human beings. The areas which are likely to get infected include the scalp, the hands and the feet. Dermatophytes, yeasts and moulds are the three major fungi responsible for skin infections. Earlier oral antifungal agents were used for treatment of fungal infection in finger and toe nails. The disadvantages of oral antifungal agents are toxicity and longer treatment period. Now medicated nail lacquers have been developed for the treatment of fungal infections i.e. onychomycosis, which has less toxicity and shorter treatment period.